1998
DOI: 10.1034/j.1600-0501.1996.090607.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone formation at dental implant dehiscence defects following guided bone regeneration and xenogeneic freeze‐dried demineralized bone matrix

Abstract: The present study evaluated rate and extent of alveolar bone formation in dental implant dehiscence defects following guided bone regeneration(GBR) and implantation of xenogeneic freeze‐dried demineralized bone matrix (xDBM). A total of 16 titanium plasma‐sprayed (TPS) and 16 hydroxyapatite‐coated (HA) titanium cylinder implants were inserted in 4 mongrel dogs following extraction of the mandibular premolar teeth. Four implant sites per jaw quadrant (2 TPS and 2 HA implant sites) were prepared into extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
41
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 0 publications
7
41
0
Order By: Relevance
“…The present results corroborate, to a certain extent, previous studies investigating a bovine-derived HA (BioOss 1 , Geistlich) (BDX) or AB for GBR in dehiscence-type defects 6,17,19 . CHO et al 6 reported a nearly complete defect fill after 12 weeks of healing following the application of either ePTFE (81%; BIC: 49%) or ePTFE + BDX (84%; BIC: 67%) at both HA-and titanium plasma-sprayed implants.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…The present results corroborate, to a certain extent, previous studies investigating a bovine-derived HA (BioOss 1 , Geistlich) (BDX) or AB for GBR in dehiscence-type defects 6,17,19 . CHO et al 6 reported a nearly complete defect fill after 12 weeks of healing following the application of either ePTFE (81%; BIC: 49%) or ePTFE + BDX (84%; BIC: 67%) at both HA-and titanium plasma-sprayed implants.…”
Section: Discussionsupporting
confidence: 95%
“…The present results corroborate, to a certain extent, previous studies investigating a bovine-derived HA (BioOss 1 , Geistlich) (BDX) or AB for GBR in dehiscence-type defects 6,17,19 . CHO et al 6 reported a nearly complete defect fill after 12 weeks of healing following the application of either ePTFE (81%; BIC: 49%) or ePTFE + BDX (84%; BIC: 67%) at both HA-and titanium plasma-sprayed implants. HOCKERS et al 17 observed a mean BIC of 17-20% for either AB + BG, BDX + BG or BG alone at machined titanium implants, even though the vertical bone growth amounted to 45% of the defect height in the BG group, to 78% in the BDX + BG group, and to 69% in the AB + BG group.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…To the best of our knowledge, these are the first histological data evaluating BOG for lateral ridge augmentation in dogs. However, the osteoconductive properties noted for BOG corroborate, to a certain extent, previous animal studies reporting on sinus floor augmentation, healing of self-contained BDs, or bone regeneration at dehiscence-type defects (Wetzel et al 1995;Cho et al 1998;Carmagnola et al 2002). When interpreting the present results, it was also observed that all grafted areas exhibited a certain amount of bone resorption between 3 and 8 weeks of healing.…”
Section: Discussionsupporting
confidence: 93%
“…Surgical creation of standardized buccal dehiscence-type defects in dogs is a commonly used model to evaluate bone regeneration at titanium implants 9,28,36,38,43 . Acute-type defects have a tendency to heal spontaneously and thus may have supported bone regeneration in all groups investigated.…”
Section: Discussionmentioning
confidence: 99%